2005
DOI: 10.1186/1471-2407-5-154
|View full text |Cite
|
Sign up to set email alerts
|

Neogenin expression may be inversely correlated to the tumorigenicity of human breast cancer

Abstract: Background: Neogenin is expressed in cap cells that have been suggested to be mammary stem or precursor cells. Neogenin is known to play an important role in mammary morphogenesis; however its relationship to tumorigenesis remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
4
29
0
1
Order By: Relevance
“…Although there is currently no clear role for RNase 4 in cancer, there are instances where unusual RNase levels have been detected in cancer patients (Peracaula et al, 2000) and RNase 4 was downregulated in our metastasising sarcoma cells. Neogenin, which is downregulated in our metastatic cells, might play a role in mammary carcinogenesis, because its expression is inversely correlated with mammary carcinogenicity (Lee et al, 2005), which again supports the pattern of expression we report here.…”
Section: Journal Of Cell Science 120 (4)supporting
confidence: 89%
“…Although there is currently no clear role for RNase 4 in cancer, there are instances where unusual RNase levels have been detected in cancer patients (Peracaula et al, 2000) and RNase 4 was downregulated in our metastasising sarcoma cells. Neogenin, which is downregulated in our metastatic cells, might play a role in mammary carcinogenesis, because its expression is inversely correlated with mammary carcinogenicity (Lee et al, 2005), which again supports the pattern of expression we report here.…”
Section: Journal Of Cell Science 120 (4)supporting
confidence: 89%
“…Neo1 expression is lost in almost 95% of invasive ductal carcinomas (Table 2) [26]. Although loss of expression is not commonly seen in breast cancer cell lines, one study found that expression was lost in a breast cancer cell model where progressive environmental insults result in incremental increases in tumorigenicity and corresponding progressive decreases in Neo1 expression [26].…”
Section: Agms In Breast Cancermentioning
confidence: 99%
“…Neo1 expression is lost in almost 95% of invasive ductal carcinomas (Table 2) [26]. Although loss of expression is not commonly seen in breast cancer cell lines, one study found that expression was lost in a breast cancer cell model where progressive environmental insults result in incremental increases in tumorigenicity and corresponding progressive decreases in Neo1 expression [26]. Knockout mouse studies have shown that NTN1/NEO1 interaction is necessary for the appropriate adhesion and stabilization of the highly proliferative cap cells of the TEB, and that loss of Ntn1 and Neo1 leads to breaks in the basal lamina, a phenomenon necessary for tumor progression [11].…”
Section: Agms In Breast Cancermentioning
confidence: 99%
“…The expression levels of Neo1 vary significantly among different cancers. For example, high expression of Neo1 was found in ESCC [13], moderate expression was displayed in pancreatic cancer [11], and low expression was revealed in breast cancer, colon cancer and glioma [7,10,12]. Our study focused on the expression of Neo1 in GC.…”
Section: Discussionmentioning
confidence: 99%